2023
DOI: 10.1021/acs.est.2c05619
|View full text |Cite
|
Sign up to set email alerts
|

Bioaccumulation and Trophic Transfer of Organophosphate Flame Retardants and Their Metabolites in the Estuarine Food Web of the Pearl River, China

Abstract: The accumulation and trophodynamics of organophosphate flame retardants (OPFRs) and their metabolites were investigated in the estuarine food web of the Pearl River, China. The mean ∑OPFR concentration among the investigated species increased in the following order: fish [431 ± 346 ng/g lipid weight (lw)] < snail (1310 ± 621 ng/g lw) < shrimp (1581 ± 1134 ng/g lw) < crab (1744 ± 1397 ng/g lw). The di-alkyl phosphates (DAPs) of di-(n-butyl) phosphate (DNBP), bis(2-butoxyethyl) phosphate (BBOEP), and diphenyl ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 62 publications
1
15
1
Order By: Relevance
“…Hydrophobicity and metabolic rates of exogenous pollutants could regulate their bioaccumulation and trophic transfer across the food web. , The log BAF values exhibited statistically significant relationships ( p < 0.01) with hydrophobicity (log K OW , r = 0.54), log metabolic rate (log K M , r = −0.74), and log molecular mass ( r = 0.53). Comparable correlations were also observed between the simulated TMF values and these parameters ( r = −0.92–0.99) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrophobicity and metabolic rates of exogenous pollutants could regulate their bioaccumulation and trophic transfer across the food web. , The log BAF values exhibited statistically significant relationships ( p < 0.01) with hydrophobicity (log K OW , r = 0.54), log metabolic rate (log K M , r = −0.74), and log molecular mass ( r = 0.53). Comparable correlations were also observed between the simulated TMF values and these parameters ( r = −0.92–0.99) (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…Five target compounds (DPPD, DTPD, BT, BTH, and 2-Me-S-BTH) with a detection rate exceeding 30% were selected to calculate their TMFs . Previous studies have confirmed that Monte Carlo simulations can effectively predict the TMF values of target compounds in the food web, even when there is no significant correlation between compound concentrations and trophic levels. , Consequently, both linear regression and Monte Carlo simulations were employed to predict the TMF values (Figures and S5). For PPDs, although no significant correlations between their levels and TLs were observed, both DPPD and DTPD displayed biomagnification trends with simulated TMF values exceeding 1 (Figure S5).…”
Section: Resultsmentioning
confidence: 99%
“…The bioaccumulation factors (BAFs) and biomagnification factors (BMFs) of CPs are calculated for biotas using eqs and . B A F s = C normalb normali normalo normalt normala / C normals normale normala normalw normala normalt normale normalr B M F s = C b i o t a 1 / C b i o t a 2 where C seawater and C biota are the average CP concentrations in seawater (ng/L) and the lipid-normalized CP concentrations in biotas (ng/g lw), respectively. , …”
Section: Methodsmentioning
confidence: 99%
“…where C seawater and C biota are the average CP concentrations in seawater (ng/L) and the lipid-normalized CP concentrations in biotas (ng/g lw), respectively. 19,35 Correlation analysis was performed to assess potential relationships and statistical significance was set at p < 0.05. Statistical analyses were conducted by SPSS 20.0 (SPSS Inc., USA) and Origin 8.5 (OriginLab Inc., USA) software.…”
Section: Sample Preparation and Instrumentalmentioning
confidence: 99%
“…Organophosphate esters (OPEs) are widely utilized as flame retardants, antifoaming agents, and plasticizers in numerous industrial and commercial products, including furniture, fabric, electronic equipment, etc. , With the restriction of brominated flame retardants, the global usage and production of OPEs have increased dramatically in recent years, as have an increasing number of environmentally relevant OPEs, and global consumption of OPEs is projected to be 86,000 tons by 2023. Recently, OPEs have been found in water samples and fish tissues from the Yangtze River, owing to their wide usage and mass production. , For instance, a total of 11 OPEs are found in water samples from the Yangtze River, and the concentrations of Σ 11 OPEs are in the range 27.9–2531 ng/L, with an average value of 225 ng/L . In addition, fish samples captured from the Yangtze River exhibit great OPE accumulation, and the levels of Σ 11 OPEs in muscle tissue vary from 122 to 2730 ng/g lipid weight .…”
Section: Introductionmentioning
confidence: 99%